Research on knowledge-sharing decisions in the logistics service supply chain - Zhao, Guanbing; Zheng, Jiamiao; Zhan, Kuijian (Frontiers in Physics, 2025)
PurposeThis study investigates the knowledge-sharing decision-making mechanisms in logistics service supply chains (LSSCs), focusing on the strategic interactions between logistics service integrators and providers.Design/methodology/approachThe study employs evolutionary game theory to model dynamic interactions in LSSCs. Numerical simulations using MATLAB are conducted to validate the theoretical findings and examine the influence of critical parameters on equilibrium outcomes.FindingsGovernment incentive subsidies can effectively promote cooperation between logistics service integrators and providers. Appropriate government incentive policies help promote fair distribution of internal revenue within the logistics service supply chain and enhance the competitiveness of the overall supply chain.Originality/valueThis study pioneers a tripartite evolutionary game model for knowledge sharing in LSSCs, analyzing the relationship between government incentives and enterprise strategies relationships. By introducing parameters such as subsidy ratios, technology maturity, and trust, it extends traditional models to address collaboration dilemmas and unlock overall supply chain value.